Photoluminescence and cathodoluminescence studies of Er3+-activated strontium molybdate for solid-state lighting and display applications. (30th November 2017) - Soni, Abhishek Kumar; Mahata, Manoj Kumar
Abstract: The photoluminescence and cathodoluminescence properties of erbium ion (Er 3+ ) activated SrMoO4 phosphor have been investigated herein. The photoluminescence (PL) emission spectra, recorded within 400–800 nm wavelength range upon 380 nm UV light excitation exhibit unusual blue emission along with its well-known green luminescence which has been explained through underlying mechanisms with the help of energy level structure. The blue luminescence of the phosphor at various Er 3+ -concentrations was further confirmed by computing the spectral colour coordinates that lies in the blue region of the chromaticity diagram. The cathodoluminescence (CL) spectra which were measured under low voltage electron beam excitation exhibited intense green luminescence. The PL and CL studies carried out in the synthesized phosphor indicates that it can be a useful candidate for making UV-excited light emitting diodes (LEDs) and low voltage electron beam excited field emission displays (FEDs).